Cases of ergotism in livestock and associated ergot alkaloid concentrations in feed - Craig, A. Morrie; Klotz, James L.; Duringer, Jennifer M. (Frontiers in Chemistry, 2015)
Ergot-induced disease was known long before Biblical times and has been the root cause for countless human epidemics spanning from the early fourteenth century to the late sixteenth century. In contrast, many of these same ergot alkaloids have been utilized for their medicinal properties to mitigate migraine headaches and have had indications as anticarcinogens. Although ergot alkaloids have been used for centuries, basic pharmacokinetic data has not been documented for clinical disease. Consequently, a threshold dose and accurate dose-response data have yet to be established. Throughout the past several years, new detection techniques have emerged to detect these alkaloids at the parts per billion which have allowed for new efforts to be made with respect to determining threshold levels and making accurate clinical diagnoses. This perspectives article provides a critical initial step for establishing a uniform interpretation of ergot toxicosis from limited existing data.